Circulating cytokine pattern and factors describing rheumatoid arthritis: IL-15 as one of the biomarkers for RA? - Pavkova Goldbergova, Monika; Pavek, Nikolas; Lipkova, Jolana; Jarkovsky, Jiri; Stouracova, Martina; Gatterova, Jindra; Vasku, Anna; Soucek, Miroslav; Nemec, Petr (Biomarkers, 2012)
The aim of study was to examine relationship among levels of cytokines (IL-6, IL-13, IL-15, TNF-α) and chemokine (IL-8), production of autoantibodies, radiographic progression, and factors describing rheumatoid arthritis (RA). A total of 156 RA patients according to ACR criteria, and 55 control subjects were recruited into study. We observed higher levels of IL-15 within RA patients compared to healthy controls. Correlations among cytokine levels and the measures of rheumatoid factors, anti-CCP, measures of disease activity, and radiographic progression were observed. We conclude that IL-15 level in circulation could serve as one of the biomarkers for RA detection.
Keywords: senioři; Peptides, Cyclic; interleukin-15; Disease Progression; senioři nad 80 let; Male; progrese nemoci; cytokiny; Middle Aged; ROC Curve; mužské pohlaví; studie případů a kontrol; Adult; mladý dospělý; Cytokines; ROC křivka; Interleukin-15; Aged, 80 and over; Young Adult; ženské pohlaví; Humans; biologické markery; autoprotilátky; Arthritis, Rheumatoid; lidé středního věku; revmatoidní artritida; dospělí; cyklické peptidy; Biomarkers; Female; Aged; Autoantibodies; lidé; Case-Control Studies